A multilevel examination of skills‐oriented human resource management and perceived skill utilization during recession: Implications for the well‐being of all workers. Issue 2 (2nd October 2018) - Okay‐Somerville, Belgin; Scholarios, Dora
Abstract : This article examines whether organizations can enhance employee well‐being by adopting human resource management (HRM) practices strategically targeted to improve skill development and deployment in a recessionary context. Employee skill utilization is proposed as the mediating mechanism between HRM practice and well‐being. The role of workplace skill composition is also examined as a boundary condition within which HRM differentially impacts employee outcomes. Using a nationally representative survey of UK workplaces (Workplace Employment Relations Survey 2011) and matched management and employee data, the analysis focused on organizations that had implemented some recessionary action following the 2008–2009 global financial and economic crisis. The findings show that human capital enhancing HRM and enriched job design positively influenced both job satisfaction and work‐related affective well‐being through increased employee skill utilization. Organizations with predominantly high‐skilled workforces were more likely to adopt these skills‐oriented HRM practices. Nevertheless, the effects of HRM on employee outcomes via skill utilization applied across organizations, regardless of workforce skill composition. The findings demonstrate employee skill utilization as a driver of HRM outcomes and the sustainability of "best practice" HRM arguments across all skill levels, even in the face of recession.